Layered oxide positive electrode material cooperatively regulated by Cu, Zn, Fe and Mg, preparation method, positive plate and battery
By developing layered oxide positive electrode materials coordinated by Cu, Zn, Fe and Mg, the problem of insufficient positive electrode materials in sodium ion battery technology is solved, and a positive electrode material with high electrochemical performance and low cost is achieved, which promotes the commercial application of sodium ion batteries.
Patent Information
- Application Number
- CN202411961735.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-18
AI Technical Summary
The existing sodium ion battery technology is immature and the lack of suitable positive electrode materials limits the commercial application of sodium ion batteries.
A layered oxide positive electrode material coordinated by Cu, Zn, Fe and Mg was developed. The chemical formula is Na0.67Ni0.145-xCu0.1Zn0.05Fe0.07Mn0.635MgxO2, which was prepared by sol-gel method or solid-phase method, with excellent rate performance and cycle stability.
The high electrochemical performance of the positive electrode material of sodium ion battery is achieved, including long cycle stability, high rate performance and low cost price, which promotes the research and development of the positive electrode material of sodium ion battery and has broad application prospects.
Smart Images

Figure CN119650685A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a layered oxide positive electrode material coordinated by Cu, Zn, Fe and Mg, a preparation method, a positive electrode sheet and a battery. Background Art
[0002] Lithium-ion batteries have the characteristics of high electrochemical capacity, excellent energy density, high energy storage conversion efficiency, and long cycle life. They have attracted widespread attention from scientists and have finally been successfully commercialized under the unremitting research of many scholars. They have been applied to many fields including portable electronics, hybrid electric vehicles, electric vehicles and other energy storage devices, bringing great convenience to mankind. However, with the gradual increase in demand for lithium resources, some challenges it faces have gradually been exposed, including insufficient reserves in the earth's crust, uneven geographical distribution, fewer resources in my country, and higher prices. Under the constraints of many factors, the cost of materials has gradually increased. With the substantial increase in demand for lithium-ion batteries at home and abroad, these factors will inevitably limit their continuous application in large-scale energy storage systems. Based on this, it is necessary to explore more suitable and more sustainable new energy storage devices. Sodium-ion batteries have gradually attracted people's attention in recent years due to their similar physical and chemical properties to lithium elements, abundant crustal resources, lower cost prices, and excellent low-temperature performance. In addition, the working principle and battery structure similar to lithium-ion batteries make it unnecessary to go to great lengths to study new production and preparation processes. After the battery technology matures, it can be directly commercialized on a large scale. Therefore, if sodium-ion batteries can be commercialized, they will be able to significantly reduce costs, thereby effectively addressing the shortage of lithium resources and achieving the continuous application and development of the energy storage market. Especially in large-scale energy storage grids, the development of sodium-ion batteries can be used as a substitute. In the future, sodium-ion batteries will be expected to be used in low-speed electric vehicles, electric ships, data centers, communication base stations, home / industrial energy storage, large-scale access to renewable energy, and smart grids. However, with the gradual deepening of research on sodium-ion batteries, some inevitable problems have also been exposed. The technology is still immature, and the lack of suitable positive electrode materials is the most prominent aspect restricting the commercialization of sodium-ion batteries.
[0003] Therefore, it is urgent to develop sodium-ion battery positive electrode materials with low cost, high electrochemical capacity, excellent rate performance and high energy density. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a layered oxide positive electrode material coordinated by Cu, Zn, Fe and Mg, a preparation method, a positive electrode sheet and a battery in view of the deficiencies in the above-mentioned prior art. The positive electrode material provided by the present invention has the characteristics of excellent rate performance and cycle stability, and the whole synthesis process is simple and the yield is high.
[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: In the first aspect of the present invention, a layered oxide positive electrode material coordinated by Cu, Zn, Fe and Mg is provided, wherein the chemical formula of the layered oxide positive electrode material is Na 0.67 Ni 0.145-x Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg x O2, where 0 <x≤0.1。
[0006] Preferably, the chemical formula of the layered oxide positive electrode material is Na 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.01 O2.
[0007] In a second aspect of the present invention, there is provided a method for preparing the layered oxide positive electrode material with coordinated regulation of Cu, Zn, Fe and Mg as described above, which method is a sol-gel method or a solid phase method.
[0008] Preferably, the steps of preparing the Cu, Zn, Fe, and Mg coordinated layered oxide positive electrode material by a sol-gel method include: S1-1. Weigh a sodium source compound, a nickel source compound, a copper source compound, a zinc source compound, an iron source compound, a manganese source compound, and a magnesium source compound according to a molar ratio, dissolve them together with a chelating agent in deionized water, stir and mix thoroughly, stir under heating until the solution is evaporated to dryness, and then heat, dry, and grind to obtain a precursor; S1-2. The precursor is subjected to a two-step calcination treatment to obtain the layered oxide positive electrode material with coordinated regulation of Cu, Zn, Fe and Mg.
[0009] Preferably, the steps of preparing the Cu, Zn, Fe, and Mg coordinated layered oxide positive electrode material by a sol-gel method include: S1-1. Weigh the sodium source compound, nickel source compound, copper source compound, zinc source compound, iron source compound, manganese source compound and magnesium source compound according to the molar ratio, dissolve them together with the chelating agent in deionized water, stir and mix thoroughly, stir at 50-90°C until the solution is evaporated to dryness, and then heat at 100-200 o C for 3-12 hours, and grind to obtain a powdery precursor; S1-2. The precursor is subjected to two-step calcination treatment in an air atmosphere: the first step is calcination treatment temperature of 350~600℃, heating rate of 2~10℃ / min, and calcination time of 4-10h; the second step is calcination treatment temperature of 700~1000℃, heating rate of 2~10℃ / min, and calcination time of 10~24h; cool to room temperature to obtain the layered oxide positive electrode material with coordinated regulation of Cu, Zn, Fe and Mg.
[0010] Preferably, when the sol-gel method is used: The sodium source compound is one or more of sodium oxalate, sodium chloride, sodium nitrate, sodium acetate and sodium citrate; The nickel source compound is one or more of nickel oxalate, nickel chloride, nickel nitrate, nickel acetate, and nickel sulfate; The copper source compound is one or more of copper oxalate, copper chloride, copper nitrate, copper acetate, and copper sulfate; The zinc source compound is one or more of zinc oxalate, zinc chloride, zinc nitrate, zinc acetate, and zinc sulfate; The iron source compound is one or more of ferric oxalate, ferric chloride, ferric nitrate, ferric acetate, and ferric sulfate; The manganese source compound is one or more of manganese oxalate, manganese chloride, manganese nitrate, manganese acetate and manganese sulfate; The magnesium source compound is one or more of magnesium oxalate, magnesium chloride, magnesium nitrate, magnesium acetate and magnesium sulfate; The chelating agent is one or more of citric acid, tartaric acid, oxalic acid and ethylenediaminetetraacetic acid.
[0011] Preferably, the steps of preparing the Cu, Zn, Fe, and Mg coordinated layered oxide positive electrode material by solid phase method include: S2-1, mixing a sodium source compound, a nickel source compound, a copper source compound, a zinc source compound, an iron source compound, a manganese source compound, and a magnesium source compound according to a molar ratio and ball-milling the mixture to obtain a precursor; S2-2, subjecting the precursor to a two-step calcination treatment to obtain the layered oxide positive electrode material with coordinated regulation of Cu, Zn, Fe and Mg.
[0012] Preferably, the steps of preparing the Cu, Zn, Fe, and Mg coordinated layered oxide positive electrode material by solid phase method include: S2-1, mixing a sodium source compound, a nickel source compound, a copper source compound, a zinc source compound, an iron source compound, a manganese source compound, and a magnesium source compound according to a molar ratio, and ball milling them at 300-500 rpm for 6-10 hours using a ball mill to obtain a precursor; S2-2, the precursor is subjected to two-step calcination treatment in air atmosphere: the first step calcination treatment temperature is 350-600°C, the heating rate is 2-10°C / min, and the calcination time is 4-10h; the second step calcination treatment temperature is 700-1000°C, the heating rate is 2-10°C / min, and the calcination time is 10-24h; cool to room temperature to obtain the layered oxide positive electrode material coordinated by Cu, Zn, Fe, and Mg; When using solid phase synthesis: The sodium source compound is one or more of sodium oxalate, sodium chloride, sodium nitrate, sodium acetate and sodium carbonate; The nickel source compound is one or more of nickel nitrate, nickel chloride, nickel acetate, nickel sulfate, nickel carbonate, and nickel oxide; The copper source compound is one or more of copper chloride, copper nitrate, copper acetate, copper sulfate, copper carbonate, and copper oxide; The zinc source compound is one or more of zinc chloride, zinc nitrate, zinc acetate, zinc sulfate, zinc carbonate, and zinc oxide; The iron source compound is one or more of ferric chloride, ferric nitrate, ferric acetate, ferric sulfate, ferric carbonate, and ferric oxide; The manganese source compound is one or more of manganese nitrate, manganese chloride, manganese acetate, manganese sulfate, manganese carbonate, and manganese oxide; The magnesium source compound is one or more of magnesium chloride, magnesium nitrate, magnesium acetate, magnesium sulfate, magnesium carbonate and magnesium oxide.
[0013] In a third aspect of the present invention, a sodium ion battery positive electrode sheet is provided, which is prepared from a positive electrode material, a conductive additive, a binder and a solvent, wherein the positive electrode material is selected from the layered oxide positive electrode material synergistically regulated by Cu, Zn, Fe and Mg as described above, or the layered oxide positive electrode material synergistically regulated by Cu, Zn, Fe and Mg prepared by the method described above.
[0014] In a fourth aspect of the present invention, a sodium ion battery is provided, comprising a positive electrode sheet, a separator, an organic electrolyte and a negative electrode metallic sodium, wherein the positive electrode sheet is the positive electrode sheet of the sodium ion battery as described in the claims.
[0015] A fifth aspect of the present invention provides an application of the above-mentioned sodium ion battery in energy storage devices such as electric vehicles, wind power generation, solar power generation, smart grid peak regulation, distributed power stations or communication bases.
[0016] The beneficial effects of the present invention are: The present invention provides a layered oxide positive electrode material coordinated by Cu, Zn, Fe and Mg, a preparation method, a positive electrode sheet and a battery. The layered oxide sodium ion battery positive electrode material provided by the present invention has excellent electrochemical properties, and the chemical formula is Na0.67 Ni 0.145-x Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg x O2, where 0≤x<0.1; the positive electrode material prepared by the present invention has long cycle stability, high rate performance and low cost price, which further promotes the research and development of positive electrode materials for sodium ion batteries; at the same time, the positive electrode material provided by the present invention is a P2 / P3 two-phase composite structure, which can better maintain structural stability, inhibit irreversible phase change, promote the transmission of sodium ions, and have better electrochemical performance. In addition, the positive electrode material provided by the present invention has a simple synthesis method, excellent electrochemical performance, is easy to mass produce, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the SEM image of the target product obtained in Example 1; Figure 2 The XRD spectrum of the target product obtained in Example 1; Figure 3 The charge and discharge curve of the target product obtained in Example 1 at a current density of 0.1C; Figure 4 The cyclic stability spectrum of the target product obtained in Example 1 at a current density of 0.1C; Figure 5 The rate performance curve of the target product obtained in Example 1 in the current density range of 0.1C-5C; Figure 6 The cyclic stability spectrum of the target product obtained in Example 1 at 1C current density; Figure 7 The cyclic stability spectrum of the target product obtained in Example 1 at a current density of 5C; Figure 8 The XRD spectrum of the target product obtained in Example 2; Fig. 9 This is a cycle stability picture of the target product obtained in Example 2 at a current density of 5C; Fig.10 This is the charge and discharge curve of the target product of Example 3 at a current density of 0.1C. DETAILED DESCRIPTION
[0018] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0019] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0020] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0021] The present invention provides a layered oxide positive electrode material with excellent cycle stability and coordinated regulation of Cu, Zn, Fe and Mg, the general chemical formula of which is Na 0.67 Ni 0.145-x Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg x O2, wherein 0≤x<0.1. The sodium ion battery positive electrode material provided by the present invention is in block shape.
[0022] In some preferred embodiments of the present invention, the positive electrode material of the sodium ion battery is Na 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.01 O2. It has the best overall performance and excellent cycle stability at 1C (1C = 173 mA g -1 After 200 cycles at a current density of 200C, the capacity retention rate is 84.3%, and after 1000 cycles at a current density of 5C, the capacity retention rate is 72.0%. In the rate performance test, the capacity retention rate is still 64.7% at current densities from 0.1 to 5C, which has greatly promoted the commercial development of sodium-ion batteries in the future.
[0023] The present invention also provides a sodium ion battery positive electrode sheet, which is prepared from an active material, a conductive additive, a binder, and a solvent, wherein: the positive electrode active material is selected from the above-mentioned synthesized Cu, Zn, Fe, Mg synergistically regulated layered oxide positive electrode material; the conductive additive is selected from one or more of carbon black, Super-P, and Ketjen black; the binder is selected from one or more of polyacrylic acid, sodium carboxymethyl cellulose, sodium alginate, and polyvinylidene fluoride; and the solvent is selected from one or more of N-methylpyrrolidone or deionized water.
[0024] The present invention also provides a method for preparing the above-mentioned sodium ion battery positive electrode sheet, which comprises: adding positive electrode material, conductive additive, and binder to a solvent in a certain proportion for mixing, and preparing the battery positive electrode sheet through subsequent coating and drying processes.
[0025] The specific methods of mixing, smearing and drying in the present invention adopt a common preparation method, which can be based on methods well known to those skilled in the art.
[0026] The present invention also provides a sodium ion battery, which is composed of a positive electrode sheet, a diaphragm, an electrolyte and a negative electrode metal sodium, wherein: the positive electrode sheet adopts the above-mentioned positive electrode sheet of the sodium ion battery. The electrolyte used is a carbonate electrolyte, and the solution concentration is 0.5~2M, preferably 1M; the solvent in the electrolyte is derived from one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, and fluorinated ethylene carbonate, preferably a mixed solvent of propylene carbonate and fluorinated ethylene carbonate; the solute in the electrolyte is selected from one or more of sodium perchlorate, sodium hexafluorophosphate, and sodium bistrifluoromethylsulfonyl imide, preferably sodium perchlorate. The diaphragm is preferably glass fiber.
[0027] The present invention also provides the application of the above-mentioned sodium ion battery in large-scale energy storage devices such as electric vehicles, solar power generation, wind power generation, smart grid peak regulation, distributed power stations or communication bases.
[0028] The present invention has the following advantages: (1) The synthesized Cu, Zn, Fe, and Mg-coordinated bulk layered oxide sodium ion battery cathode material has the chemical formula Na 0.67 Ni 0.145-x Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg x O2 (0≤x<0.1) has greatly promoted the future commercial development of sodium-ion battery material systems.
[0029] (2) Na of the present invention 0.67 Ni 0.145-x Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg x O2 (0≤x<0.1) positive electrode material has excellent cycle stability and rate performance, low cost, and is a very promising positive electrode material for sodium ion batteries.
[0030] (3) Na provided in the relatively best embodiment of the present invention 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.01O2 cathode material has the best cycle stability at 1C (1C=173 mA g -1 After 200 cycles at a current density of 2C, its capacity retention rate is 84.3%, and after 1000 cycles at a current density of 5C, its capacity retention rate is 72.0%. In the rate performance test, the capacity retention rate is still 64.7% at current densities from 0.1 to 5C, which makes it an ideal positive electrode material for preparing sodium-ion battery energy storage devices.
[0031] (4) The positive electrode material synthesized by the method of the present invention has better comprehensive performance than the material not regulated by multiple metals.
[0032] The above is the overall concept of the present invention. In order to further understand the present invention, the excellent performance layered oxide sodium ion battery positive electrode material provided by the present invention and its preparation method and application are described below in combination with specific examples. The protection scope of the present invention is not limited by the following embodiments. Example
[0033] Step 1: Preparation of Na by sol-gel method 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.01 O2 cathode material S1-1. Weigh the raw materials according to the molar ratio: sodium acetate, nickel acetate, copper acetate, zinc acetate, iron acetate, manganese acetate, and magnesium acetate. Dissolve the raw materials and chelating agent citric acid in deionized water. The ratio of the sum of the molar amounts of sodium acetate, nickel acetate, copper acetate, zinc acetate, iron acetate, manganese acetate, and magnesium acetate to the molar amount of citric acid is 1:2. Use a magnetic stirrer to stir continuously until the mixture is uniform. Then, place in a constant temperature oil bath at 70°C, stir until the solution is evaporated to dryness, and then transfer the sample to 150 o C high temperature oven for 6 h, and then taken out after cooling to room temperature. The obtained sample was ground in a mortar to obtain a powdery precursor.
[0034] S1-2, the precursor is placed in a muffle furnace and calcined in two steps under air atmosphere: the first step of pre-calcination is a heating temperature of 450 ° C, a heating rate of 2 ° C / min, and a holding time of 6 hours; the second step is high-temperature calcination, the temperature is raised to 850 ° C, the heating rate is 2 ° C / min, the holding time is 15 hours, and the temperature is cooled to room temperature to obtain the target product: positive electrode material Na 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe 0.0 7Mn 0.635 Mg 0.01O2.
[0035] Step 2, preparing the positive electrode sheet of the sodium ion battery: The Na 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.01 O2 positive electrode material, Super P and polyvinylidene fluoride binder (PVDF) were mixed in a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone was added as a solvent. After the steps of mixing machine slurry, smearing, drying, weighing, etc., a Na 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.0 1O2 active material sodium ion battery positive electrode.
[0036] Step 3, assemble with Na 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.01 Sodium ion battery with O2 material as positive electrode: The sodium ion battery positive electrode sheet prepared above and metallic sodium were assembled into a sodium ion half-cell in a glove box, GF / F was selected as the battery separator, and carbonate electrolyte (1M NaClO4in PC) was selected as the electrolyte.
[0037] Figure 1 The figure shows the SEM image of the positive electrode material prepared in Example 1. It can be seen from the figure that the overall block morphology of the material is evenly distributed in the entire viewing angle.
[0038] Figure 2 The XRD image of the positive electrode material obtained in Example 1 is shown. It can be seen from the image that the synthesized positive electrode material has a P2 / P3 two-phase structure.
[0039] Figure 3 The figure shows the sodium ion battery assembled with the positive electrode material obtained in Example 1 at 0.1C (1C = 173 mA g -1 ) charge-discharge curves at current density. It can be seen from the figure that the synthesized material has a charge-discharge capacity of 109.6 mAh g in sodium ion batteries. -1 Higher discharge specific capacity.
[0040] Figure 4The figure shows the cycle stability test result of the sodium ion battery assembled with the positive electrode material obtained in Example 1 at a current density of 0.1C. It can be seen from the figure that after 100 cycles, there is still a capacity retention rate of 86.0%.
[0041] Figure 5 The figure shows the rate performance spectrum of the positive electrode material obtained in Example 1 in the range of 0.1C-5C. It can be seen from the figure that it exhibits relatively good electrochemical capacity under current density conditions from 0.1C to 5C, has a capacity retention rate of 64.7%, and exhibits excellent rate performance.
[0042] Figure 6 The figure shows the cycle stability test result of the sodium ion battery assembled with the positive electrode material obtained in Example 1 at a current density of 1C. It can be seen from the figure that after 200 cycles, there is still a capacity retention rate of 84.3%.
[0043] Figure 7 The figure shows the cycle stability test result of the sodium ion battery assembled with the positive electrode material obtained in Example 1 at a current density of 5C. It can be seen from the figure that after 1000 cycles, there is still a capacity retention rate of 72.0%. Example
[0044] The preparation method is the same as that in Example 1, except that the raw materials are divided into 0.67 Ni 0.115 Cu 0.1 Zn 0.0 5Fe 0.07 Mn 0.635 Mg 0.03 O2 was added in a stoichiometric ratio.
[0045] Figure 8 The Na obtained in Example 2 is shown. 0.67 Ni 0.115 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.03 XRD diagram of O2 material. It can be seen from the figure that the synthesized positive electrode material has good crystallinity and is also a P2 / P3 mixed phase structure.
[0046] Fig. 9 The Na obtained in Example 2 is shown. 0.67 Ni 0.115 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.03The cycling stability of sodium-ion batteries assembled with O2 positive electrode materials at a current density of 5C shows that the capacity retention rate is only 50.7% after 1000 cycles. Example
[0047] Step 1, solid phase synthesis method to prepare Na 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.01 O2 cathode material Sodium carbonate, nickel oxide, copper oxide, zinc oxide, iron oxide, manganese oxide, and magnesium oxide were placed in a ball mill according to a stoichiometric ratio, and ball milled at 400 rpm for 8 h using a ball mill to obtain a precursor powder; The precursor sample was placed in a crucible and then calcined in two steps under air atmosphere: the first step of pre-calcination was heated to 450°C at a heating rate of 2°C / min for 6 hours; the second step of high-temperature calcination was heated to 850°C at a heating rate of 2°C / min for 15 hours, and then cooled to room temperature to obtain the target product: positive electrode material Na 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.01 O2.
[0048] Step 2: Preparation of positive electrode for sodium ion battery The Na 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.01 O2 positive electrode material, Super P and polyvinylidene fluoride binder (PVDF) were mixed in a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone was added as a solvent. After the steps of mixing machine slurry, coating, drying, etc., a Na 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.01 Sodium ion battery positive electrode sheet with O2 positive electrode active material.
[0049] Step 3, assemble with Na 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe0.07 Mn 0.635 Mg 0.01 Sodium ion battery with O2 material as the positive electrode.
[0050] The sodium ion battery prepared above was assembled with the sodium ion battery positive electrode sheet and the metallic sodium negative electrode, GF / F was used as the battery separator, and the electrolyte was a carbonate electrolyte (1M NaClO4in PC).
[0051] Fig.10 The figure shows the sodium ion battery assembled with the positive electrode material obtained in Example 3 at 0.1C (1C = 173 mA g -1 ) charge-discharge curve at current density. It can be seen from the figure that 92.14 mAh g can be released during the initial cycle. -1 electrochemical specific capacity.
[0052] Comparative Examples 1, 2, 3, and 4 are provided. The preparation methods of the comparative examples are the same as those of Example 1, except that the raw materials in Comparative Examples 1-4 are respectively prepared according to the ratio of Na 0.67 Ni 0.235 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.01 O2, Na 0.67 Ni 0.185 Cu 0.1 Fe 0.07 Mn 0.635 Mg 0.01 O2, Na 0.67 Ni 0.17 Cu 0.1 Zn 0.05 Mn 0.67 Mg 0.01 O2, Na 0.67 Ni 0.145 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 O2 is added in a stoichiometric ratio. The test results of the comparative examples all show lower cycle stability than that of Example 1: The capacity retention rate of comparative example 1 after 1000 cycles at a current density of 5C is 60.3%; the capacity retention rate of comparative example 2 after 1000 cycles at a current density of 5C is 54.1%; the capacity retention rate of comparative example 3 after 1000 cycles at a current density of 5C is 64.4%; the capacity retention rate of comparative example 4 after 1000 cycles at a current density of 5C is 66.5%; From the above results, it can be explained that the composite doping of the four elements Cu, Zn, Fe and Mg has a synergistic enhancement effect in improving the cycle stability performance.
[0053] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A layered oxide positive electrode material coordinated by Cu, Zn, Fe and Mg, characterized in that: The chemical formula of the layered oxide cathode material is Na 0.67 Ni 0.145-x Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg x O2, where 0 <x≤0.1。 2. The layered oxide positive electrode material coordinated by Cu, Zn, Fe and Mg according to claim 1, characterized in that: The chemical formula of the layered oxide cathode material is Na 0.67 Ni 0.135 Cu 0.1 Zn 0.05 Fe 0.07 Mn 0.635 Mg 0.01 O2.
3. A method for preparing a layered oxide positive electrode material synergistically regulated by Cu, Zn, Fe and Mg as claimed in claim 1 or 2, characterized in that: The method is a sol-gel method or a solid phase method.
4. According to the method for preparing the Cu, Zn, Fe, and Mg coordinated layered oxide positive electrode material according to claim 3, the steps of preparing the Cu, Zn, Fe, and Mg coordinated layered oxide positive electrode material by a sol-gel method include: S1-1. Weigh a sodium source compound, a nickel source compound, a copper source compound, a zinc source compound, an iron source compound, a manganese source compound, and a magnesium source compound according to a molar ratio, dissolve them together with a chelating agent in deionized water, stir and mix thoroughly, stir under heating until the solution is evaporated to dryness, and then heat, dry, and grind to obtain a precursor; S1-2. The precursor is subjected to a two-step calcination treatment to obtain the layered oxide positive electrode material with coordinated regulation of Cu, Zn, Fe and Mg.
5. According to the method for preparing the Cu, Zn, Fe, and Mg coordinated layered oxide positive electrode material according to claim 4, the steps of preparing the Cu, Zn, Fe, and Mg coordinated layered oxide positive electrode material by a sol-gel method include: S1-1. Weigh the sodium source compound, nickel source compound, copper source compound, zinc source compound, iron source compound, manganese source compound and magnesium source compound according to the molar ratio, dissolve them together with the chelating agent in deionized water, stir and mix thoroughly, stir at 50-90°C until the solution is evaporated to dryness, and then heat at 100-200 o C for 3-12 hours, and grind to obtain a powdery precursor; S1-2. The precursor is subjected to two-step calcination treatment in an air atmosphere: the first step is calcination treatment temperature of 350~600℃, heating rate of 2~10℃ / min, and calcination time of 4-10h; the second step is calcination treatment temperature of 700~1000℃, heating rate of 2~10℃ / min, and calcination time of 10~24h; cool to room temperature to obtain the layered oxide positive electrode material with coordinated regulation of Cu, Zn, Fe and Mg.
6. The method for preparing the layered oxide positive electrode material coordinated by Cu, Zn, Fe and Mg according to claim 4, when the sol-gel method is used: The sodium source compound is one or more of sodium oxalate, sodium chloride, sodium nitrate, sodium acetate and sodium citrate; The nickel source compound is one or more of nickel oxalate, nickel chloride, nickel nitrate, nickel acetate, and nickel sulfate; The copper source compound is one or more of copper oxalate, copper chloride, copper nitrate, copper acetate, and copper sulfate; The zinc source compound is one or more of zinc oxalate, zinc chloride, zinc nitrate, zinc acetate, and zinc sulfate; The iron source compound is one or more of ferric oxalate, ferric chloride, ferric nitrate, ferric acetate, and ferric sulfate; The manganese source compound is one or more of manganese oxalate, manganese chloride, manganese nitrate, manganese acetate and manganese sulfate; The magnesium source compound is one or more of magnesium oxalate, magnesium chloride, magnesium nitrate, magnesium acetate and magnesium sulfate; The chelating agent is one or more of citric acid, tartaric acid, oxalic acid and ethylenediaminetetraacetic acid.
7. The method for preparing the Cu, Zn, Fe, and Mg coordinated layered oxide positive electrode material according to claim 3, wherein the steps of preparing the Cu, Zn, Fe, and Mg coordinated layered oxide positive electrode material by a solid phase method include: S2-1, mixing a sodium source compound, a nickel source compound, a copper source compound, a zinc source compound, an iron source compound, a manganese source compound, and a magnesium source compound according to a molar ratio and ball-milling the mixture to obtain a precursor; S2-2, subjecting the precursor to a two-step calcination treatment to obtain the layered oxide positive electrode material with coordinated regulation of Cu, Zn, Fe and Mg.
8. The method for preparing the Cu, Zn, Fe, and Mg coordinated layered oxide positive electrode material according to claim 7, wherein the steps of preparing the Cu, Zn, Fe, and Mg coordinated layered oxide positive electrode material by a solid phase method include: S2-1, mixing a sodium source compound, a nickel source compound, a copper source compound, a zinc source compound, an iron source compound, a manganese source compound, and a magnesium source compound according to a molar ratio, and ball milling them at 300-500 rpm for 6-10 hours using a ball mill to obtain a precursor; S2-2, the precursor is subjected to two-step calcination treatment in air atmosphere: the first step calcination treatment temperature is 350-600°C, the heating rate is 2-10°C / min, and the calcination time is 4-10h; the second step calcination treatment temperature is 700-1000°C, the heating rate is 2-10°C / min, and the calcination time is 10-24h; cool to room temperature to obtain the layered oxide positive electrode material coordinated by Cu, Zn, Fe, and Mg; When using solid phase synthesis: The sodium source compound is one or more of sodium oxalate, sodium chloride, sodium nitrate, sodium acetate and sodium carbonate; The nickel source compound is one or more of nickel nitrate, nickel chloride, nickel acetate, nickel sulfate, nickel carbonate, and nickel oxide; The copper source compound is one or more of copper chloride, copper nitrate, copper acetate, copper sulfate, copper carbonate, and copper oxide; The zinc source compound is one or more of zinc chloride, zinc nitrate, zinc acetate, zinc sulfate, zinc carbonate, and zinc oxide; The iron source compound is one or more of ferric chloride, ferric nitrate, ferric acetate, ferric sulfate, ferric carbonate, and ferric oxide; The manganese source compound is one or more of manganese nitrate, manganese chloride, manganese acetate, manganese sulfate, manganese carbonate, and manganese oxide; The magnesium source compound is one or more of magnesium chloride, magnesium nitrate, magnesium acetate, magnesium sulfate, magnesium carbonate and magnesium oxide.
9. A sodium ion battery positive electrode sheet, prepared from a positive electrode material, a conductive additive, a binder and a solvent, characterized in that: The positive electrode material is selected from the layered oxide positive electrode material with coordinated regulation of Cu, Zn, Fe and Mg as described in claim 1 or 2, or the layered oxide positive electrode material with coordinated regulation of Cu, Zn, Fe and Mg prepared by the method as described in any one of claims 3 to 8.
10. A sodium ion battery comprising a positive electrode sheet, a separator, an organic electrolyte and a negative electrode metallic sodium, characterized in that: The positive electrode sheet is the positive electrode sheet for a sodium ion battery according to claim 9.
Citation Information
Patent Citations
Sodium ion secondary battery, and layered titanate active substance, electrode material, anode and cathode adopted by the sodium ion secondary battery, and preparation method of the layered titanate active substance
CN103456936A
Multi-metal co-regulated layered oxide sodium-ion battery positive electrode material as well as preparation method and application thereof
CN115939369A
P-phase-like layered sodium transition metal oxide positive electrode material, preparation method and battery
CN117577824A
P2 and P3 mixed phase layered oxide sodium-ion battery positive electrode material as well as preparation method and application thereof
CN118136830A
Sodium-ion battery high-entropy layered positive electrode material, preparation method and battery
CN118248865A
Cited By
Negative electrode based on phase-change material modified zinc powder, preparation method of negative electrode and aqueous zinc ion battery
CN122246039A